Perbandingan Bermain Bebas dan Bermain Komando Pada Pembelajaran Luar Ruangan di Pendidikan Anak Usia Dini Yogyakarta - Hidayat, Afif Khoirul; Hasanah, Nurlayli (Generasi Emas, 2024)
This study aims to compare the quality and impact of free play and structured play learning processes in supporting early childhood development within the outdoor learning environments of PAUD Yogyakarta. A comparative descriptive methodology was employed, involving 177 students from five State Kindergartens in Yogyakarta. Data were collected through observations using a sheet that included indicators of active engagement, safety, social interaction, exploration, creativity, problem-solving, discipline, and emotional management. The results reveal that free play is more effective in supporting active engagement, exploration, and creativity in children, while structured play better supports safety and discipline. Independent t-tests were conducted on the data from the free play and structured play learning processes to determine whether significant differences existed between the two play activities. The findings indicate a substantial difference between the methods, with a p-value of 0.039455, below the significance threshold of 0.05, showing that free play has a more positive impact on child development. According to the data, free play excels in terms of active engagement (96.63%), social interaction (83.15%), exploration (94.38%), creativity (77.53%), problem-solving (79.78%), and emotional management (71.91%). Conversely, structured play supports safety (98.86%) and discipline (94.32%). This research has implications for the future learning process in early childhood education in Yogyakarta, as it helps teachers and school principals realize the importance of outdoor learning activities in free play to support the holistic development of children.